2014
DOI: 10.3892/mmr.2014.2524
|View full text |Cite
|
Sign up to set email alerts
|

Milk thistle seed extract protects rat C6 astroglial cells from acute cocaine toxicity

Abstract: Cocaine is a powerful addictive drug, widely abused in most Western countries. It easily reaches various domains within and outside of the central nervous system (CNS), and triggers varying levels of cellular toxicity. No pharmacological treatment is available to alleviate cocaine-induced toxicity in the cells without side-effects. Here, we discerned the role of milk thistle (MT) seed extract against cocaine toxicity. First, we investigated acute cytotoxicity induced by treatment with 2, 3 and 4 mM cocaine for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Our data provide compelling evidence to support the hypothesis that inhibition of the early response changes by NAC enhances cell survival through increased GSH levels. Compounds which support GSH synthesis could therefore mitigate toxicity of early response events in cells exposed to cocaine [ 22 ]. The recapitulation of cocaine-induced changes observed in our model (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data provide compelling evidence to support the hypothesis that inhibition of the early response changes by NAC enhances cell survival through increased GSH levels. Compounds which support GSH synthesis could therefore mitigate toxicity of early response events in cells exposed to cocaine [ 22 ]. The recapitulation of cocaine-induced changes observed in our model (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these properties demonstrate that C6 cell cultures behave like an astroglia-like cell line. In the past, C6 cells have also been used extensively for in vitro drug abuse research [ 7 , 8 , 19 22 ] and in the study of astrocytic function [ 23 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glutamatergic neurons feature prominently in C1, C3, C21, and C33. Studies on rats have shown that cocaine is toxic to astrocytes and that loss of astrocytes leads to dysfunctional neuron-glia communication (Badisa et al 2013(Badisa et al , 2014(Badisa et al , 2015. Eaat1, which is highly expressed in astrocytes (Supplemental Table S4), encodes a transmembrane glutamate transporter involved in glia-neuron communication (MacNamee et al 2016).…”
Section: Cocaine-modulated Gene Expression In Gliamentioning
confidence: 99%